Correlation analysis of the development of the transport and logistics system of Kazakhstan - Rakhmetulina А.А.; Kulmaganbetova, A.S.; Raimbekov, Zh.S. (BUKETOV BUSINESS REVIEW, 2024)
Object: to analyze the indicators of the international rating and the state of development of the transport and logistics system of Kazakhstan, on the basis of which to identify the factors contributing to its development. Methods: The paper uses the method of correlation analysis between the rating indicators of logistics in Kazakhstan and statistical metrics of the transport and logistics system of the Republic of Kazakhstan. Findings: The article presents an analysis of the transport and logistics system of the Republic of Kazakhstan. The positions of Kazakhstan in the world rankings (Logistics Performance Index, Transport infrastructure / The Global Competitiveness Index, Emerging Market Logistics Index) are analyzed. Based on the analysis of the rating, an assessment of the effectiveness of organizational and economic instruments for the development of the transport and logistics system of Kazakhstan is given. Conclusions: The transport and logistics system is an important component for the economy of Kazakhstan. The geographical location gives Kazakhstan a huge advantage to participate in international logistics, as it is located in the very center of the Eurasian continent. This allows Kazakhstan to develop as a link between Asia and Europe, providing transit of goods in the East-West and North-South directions. The activities of the TLS are very important for the country. There is a number of systemic problems in the transport and logistics system of Kazakhstan, which may negatively affect the growth rate of the economy in the future. In the study, the authors systematized the factors of sustainable development of transport and logistics systems, considered the trends that will affect the transport and logistics industry in the near future. A correlation has also been established between the main indicators of the development of the transport and logistics system and the EMLI index of Kazakhstan, which determines the importance of comparing their own results with the results of the most developed countries in logistics.